REPRESENTASI TOLAK REKLAMASI TELUK BENOA DALAM KARIKATUR SAMPUL MAJALAH BOG-BOG CARTOON EDISI APRIL 2016 - Julianditya Dharmayanti, Pande Made; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2017)
Benoa Bay Reclamation was emerging the pros and cons in the middle of Balinese life that bring out an action called Reclamation Refusal. It was a real form of society refusal to the huge project development that will be declared. Bog-Bog as one of the mass media in the form of caricature magazine; represented the phenomenon which already happened on its April 2016 edition. The purpose of this study is to determine the representation of the Benoa Bay Reclamation Refusal in caricature cover of Bog-Bog Bali Cartoon magazine on April 2016 edition. To achieve the aims, the research was conducted using semiotic analysis method proposed by Charles Sanders P eir ce by qualitative research and constructivist paradigm. The result of this study was Bog-Bog Bali Cartoon magazine represented the reclamation refusal movement that based on Bali local genius concept called “Tri Hita Karana”. Parhyangan contained in caricatures of Balinese Women, Legong Dancers, pecalang caricature, Baris Dancers, and flute Players. Meanwhile, the Pawongan value was described on Made Bogler caricature and Traders caricature. Further, the Palemahan contained in, Excavator, water, Soil, Surfing Players, Sea Fish, , pigs and dogs caricature. Hence, Bog-Bog Bali Cartoon magazine demonstrates the caricature function as a medium of social criticism of ongoing gover n ment policy 51 since 2014 and Balinese people apprehension on the reclamation issues in Bali. Keywords: Bog-Bog Bali Cartoon Magazine , Caricature , Reclamation Refusal, Representation